Trait‐modulated decline of carabid beetle occurrence along elevational gradients across the European Alps. (17th January 2020) - Chamberlain, Dan; Gobbi, Mauro; Negro, Matteo; Caprio, Enrico; Palestrini, Claudia; Pedrotti, Luca; Brandmayr, Pietro; Pizzolotto, Roberto; Rolando, Antonio
Abstract: Aim: To assess how species traits modulate the responses of carabids to elevational gradients, and how consistent these relationships are across different Alpine regions. Location: Italian Alps. Taxon: Coleoptera, Carabidae (ground beetles). Methods: Carabid communities were sampled using pitfall traps along elevational gradients (697–2, 840 m) in 416 study sites comprising a range of habitat types. The probability of carabid occurrence was modelled in relation to elevation and its interaction with two key traits, body size and wing development, using a mixed‐modelling framework. The consistency of these associations was then assessed across three geographically separated regions. Results: Carabid occurrence declined with increasing elevation, although this relationship was modulated by both body size and wing development. Smaller species were less likely to occur than larger‐bodied species at lower elevations. There was a steep decline in occurrence of larger species from low to high elevation, but a slight increase in smaller species, when considering all regions combined. All wing development types declined with elevation, most notably for brachypterous (reduced wings) species. However, these patterns also varied regionally, especially for wing development, indicating that trait‐elevation interactions are not geographically consistent. Habitat could not explain the differences between regions for body size, but was likely an important driver of regional differences in the role of wing development on carabid occurrence. Main conclusions: Species traits are important in explaining the distribution of carabids along elevational gradients in mountains, and they may help to identify the species that are the most vulnerable, and the most resilient, to future environmental change. Increased probability of occurrence of smaller species at higher elevations suggests that they may be particularly vulnerable to environmental change in the future. However, the difference in responses to elevation between regions has important implications for modelling species distributions, as it suggests low model transferability, that is, a trait‐based model derived from one region cannot necessarily be used to project relative elevational shifts in a wider area.